Untangling the concept of coercive control: theorizing domestic violent crime - Walby, Sylvia (Criminology & criminal justice, 2018)
The article assesses three approaches to domestic violence: two that use the concept of ‘coercive control’ and one that uses ‘domestic violent crime’. These are: Stark’s concept of coercive control; Johnson’s distinction between situational couple violence and intimate terrorism, in which coercive control is confined to the latter; and that of domestic violent crime, in which all physical violence is conceptualized as coercive and controlling. The article assesses these three approaches on seven issues. It offers original analysis of data from the Crime Survey for England and Wales concerning variations in repetition and seriousness in domestic violent crime. It links escalation in domestic violent crime to variations in the economic resources of the victim. It concludes that the concept of domestic violent crime is preferable to that of coercive control when seeking to explain variations in domestic violence.